2013
DOI: 10.26874/kjif.v1i1.24
|View full text |Cite
|
Sign up to set email alerts
|

EFEK ANTIDIARE EKSTRAK ETANOL DAUN MINDI (Melia azedarach Linn) PADA MENCIT SWISS WEBSTER JANTAN

Abstract: ABSTRAKMindi merupakan salah satu tumbuhan yang digunakan di masyarakat sebagai antidiare. Penelitian ini bertujuan untuk mengetahui efek antidiare ekstrak etanol daun mindi terhadap mencit Swiss Webster jantan. Ekstrak etanol dibuat dengan menggunakan seperangkat alat Soxhlet. Pengujian efek antidiare dilakukan dengan metode transit intestinal dan metode proteksi diare yang diinduksi oleh Oleum ricini. Data dianalisis statistik menggunakan Uji-t dan Anova. Hasil penelitian menunjukan bahwa kelompok uji ekstra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Feces consistency is determined by scoring the feces; namely, a score of 1 for normal feces, score 2 for slightly soft feces, score 3 for very soft feces, and score 4 for soft liquid feces. The smaller the feces consistency value, the greater the anti-diarrhea effect produced [23]. The positive control group showed that the consistency of the stool changed back to the normal stool at 64 h. The extract ethanol melinjo leaves also had an effect on changing the consistency of feces to normal or healing diarrhea in rats.…”
Section: Feces Consistencymentioning
confidence: 92%
“…Feces consistency is determined by scoring the feces; namely, a score of 1 for normal feces, score 2 for slightly soft feces, score 3 for very soft feces, and score 4 for soft liquid feces. The smaller the feces consistency value, the greater the anti-diarrhea effect produced [23]. The positive control group showed that the consistency of the stool changed back to the normal stool at 64 h. The extract ethanol melinjo leaves also had an effect on changing the consistency of feces to normal or healing diarrhea in rats.…”
Section: Feces Consistencymentioning
confidence: 92%
“…The content of tannin and flavonoid compounds in extracts of red shoots of Syzygium myrtifolium Walp are suspected to have antidiareal activity. Tanin acts as an antidiarrheal which works as an adstringentia mechanism, able to shrink the mucous membrane of the intestine and strengthen the intestinal wall sothe possibility of blocking the absorption of bacteria and toxins while reducing fluid expenditure [11].…”
Section: Antidiarrheal Testmentioning
confidence: 99%
“…In determining the consistency of faeces done by looking at the shape that occurs it can be categorized into four groups, namely not chapter (0), normal (1), soft (2), and slimy/watery (3). Consistency seen visually was assessed using Scoring, so that groups that were declared to have antidiarrheal effects were the group that showed the smallest consistency rate (Suherman et al, 2013). group.…”
Section: Stool Consistencymentioning
confidence: 99%
“…group. The smaller the number of stool consistency, the greater the antidiare effect produced (Suherman et al, 2013). The results of the study of ethanol extract of the leaves of V. amygdalina 400 mg/kg BW which have the best effect as antidiarrheal are associated with a corresponding increase in dosage, the effect also increases (Nurhalimah et al, 2015).…”
Section: Stool Consistencymentioning
confidence: 99%